Teaching visual discrimination to the educable mentally retarded through fading of stimulus contrasts - Cornejo, Aida M. 1930-; Sison, Waldetrudes Montojo (Quezon City College of Education, University of the Philippines Diliman, 1975)
This is an individual study using a non schooling mentally retarded child. It introduces teachers to the recent trend in research on mental retardation involving gradual change in discrimination ability. The technique employed is the fading procedure, i.e., the gradual withdrawal of stimulus contrasts. Results paralleled those of the findings in Dimension A. The fading procedure is found successful in the subject's discrimination of stimulus contrasts involving color and color name for the first part of the training procedure and shape and name of the shape in the second
Thesis (Master of Arts in Teaching Special Education - Mental Retardation)--University of the Philippines, Diliman
Keywords: Visual discrimination; Behavior disorders in adolescence -- Philippines; Children with mental disabilities -- Education -- Philippines; Special education -- Philippines